Older Workers’ Job Satisfaction as a Factor in the Extension of Employment in Slovenia and the EU - Aristovnik, Aleksander; Jaklič, Ksenja (Naše gospodarstvo/Our economy, 2013)
The purpose of this article is to compare older workers’ job satisfaction in Slovenia to that in the EU in order to analyse its various dimensions as well as specifics regar- ding age, gender, sector of activity, and type of occupation; it also seeks to identify what determines older workers’ job satisfaction most. Using data from Eurofound’s Fifth European Working Conditions survey in 2010, the statistical analysis indica- tes that Slovenia, which had the lowest employment rate of older people in the EU in 2011, ranks 15th among member states and below the EU average. Slovenia’s older workers, like their European colleagues, are most satisfied with the recognition of job well done and least satisfied with the opportunities for promotion. Compared with other member states, Slovenia’s older workers are relatively dissatisfied with their working conditions, salary, and adequacy of motivation for committed work while being relatively satisfied with the recognition of job well done and colleagu- es. Older workers’ job satisfaction is mostly determined based on the adequacy of motivation for committed work.